Global ubiquitinome profiling identifies NEDD4 as a regulator of Profilin 1 and actin remodelling in neural crest cells - Iman Lohraseb; Peter McCarthy; Genevieve Secker; Ceilidh Marchant; Jianmin Wu; Naveid Ali; Sharad Kumar; Roger J. Daly; Natasha L. Harvey; Hiroshi Kawabe; Oded Kleifeld; Sophie Wiszniak; et al. (Nature Communications, 2022)
Here the authors combine multi-omics approaches to uncover a role for ubiquitination and the ubiquitin ligase NEDD4 in targeting the actin binding protein Profilin 1 to regulate actin polymerisation in neural crest cells.